A Bayesian approach to rapid seismic vulnerability assessment at urban scale. Issue 1 (2nd January 2018) - Campostrini, Gian Paolo; Taffarel, Sabrina; Bettiol, Giulia; Valluzzi, Maria Rosa; Da Porto, Francesca; Modena, Claudio
ABSTRACT: The seismic vulnerability of city centers is commonly assessed by extending the study methods applied to single buildings to urban aggregations. This approach is not always applicable at territorial scale, as it is uneconomical in terms of time and costs. An innovative method provides reasonable large-scale a priori estimation of parameters not directly evaluable from the exterior of buildings by elaborating values which can be measured from the outside. Those parameters are treated as continuous variables, by assigning them a suitable probability density function. The Bayesian approach is adopted, which allows the update of initial hypotheses by using new data gathered during on-site surveys. In this regard, a rapid survey form for the on-site data collection is proposed. An example of its application to a façade of a building structural unit in Santo Stefano di Sessanio in L'Aquila province (Italy) is proposed, showing promising preliminary results for buildings belonging to Italian historical centers.